Diagnostic Expert System for Children with Mental Disabilities with the Certainty Factor Method - Yunasdi Genta Fortuna (Universitas Putra Indonesia YPTK Padang, 2022)
Mental retardation is a mental disability which is also known as Intellectual Disability or mental retardation. Intellectual Disability is characterized by significant limitations in intellectual functioning, significant limitations in adaptive behavior, including cognitive, social, and practical adaptive skills. SLB YPAC West Sumatra is one of the special schools that prioritizes quality services for people with disabilities to increase independence. These services need to be carried out to minimize obstacles or disturbances of repetitive, aggressive behavior and other balance disorders. At SLB YPAC West Sumatra, 100% still use experts for their services. With the problems that exist in SLB YPAC West Sumatra which still uses a manual system, an expert system is created that can diagnose children with mental retardation using the Certainty Factor method. By using data on types of mental retardation and some symptoms, it was found that mentally retarded people at SLB YPAC West Sumatra suffer from moderate mental retardation with a CF value of 0.33. This research is expected to help SLB YPAC West Sumatra and service to be faster and also help the performance of employees at SLB YPAC West Sumatra